2003
DOI: 10.1086/379324
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mannose-Binding Lectin on Susceptibility to Infectious Diseases

Abstract: When the adaptive immune response is either immature or compromised, the innate immune system constitutes the principle defense against infection. Mannose-binding lectin (MBL) is a C-type serum lectin that plays a central role in the innate immune response. MBL binds microbial surface carbohydrates and mediates opsonophagocytosis directly and by activation of the lectin complement pathway. A wide variety of clinical isolates of bacteria, fungi, viruses, and parasites are bound by MBL. Three polymorphisms in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
322
2
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(340 citation statements)
references
References 71 publications
8
322
2
8
Order By: Relevance
“…These data illustrate that L-ficolin activity may be closely related to disease progression. An increased MBL concentration in HCV patients in comparison to controls and a link to more severe hepatitis has been shown previously (36). MBL/MASP-1 complex activities were closely related to disease progression (37).…”
Section: Binding Of L-ficolin To E1-and E2-expressing Cells Triggers supporting
confidence: 65%
“…These data illustrate that L-ficolin activity may be closely related to disease progression. An increased MBL concentration in HCV patients in comparison to controls and a link to more severe hepatitis has been shown previously (36). MBL/MASP-1 complex activities were closely related to disease progression (37).…”
Section: Binding Of L-ficolin To E1-and E2-expressing Cells Triggers supporting
confidence: 65%
“…1 These proteins play a role in first-line host defence and are therefore known as defence collagens and those that are lectins are also named collectins (collagen and lectin). Over the past 10 to 15 years MBL has been the focus of interest for several research groups around the world owing to its putative clinical role, especially based on epidemiological studies that have suggested that genetically determined variation in MBL serum concentration influences the susceptibility to and course of different types of infections as well as autoimmune, metabolic and cardiovascular diseases (for recent reviews see Turner and Hamvas 2 , Kilpatrick 3 , Eisen and Minchinton 4 , and Nuytinck and Shapiro 5 ). In particular, MBL may have some importance during the period from the time at which the maternalderived antibodies disappear to the time at which the child's own immune system is being matured and in the lag phase before a primary immune response is generated following microbial challenges.…”
Section: Introductionmentioning
confidence: 99%
“…1 Deficiency of MBL, based on genetic polymorphisms, is a relatively common observation and is reported to increase susceptibility to infectious disease in children and adults. 2,3 Although results are somewhat conflicting, most studies emphasize the importance of MBL in immune-compromised hosts. In patients with a hematological malignancy receiving chemotherapy, increased susceptibility to infection and prolonged duration of febrile neutropenic episodes were associated with MBL deficiency.…”
Section: Introductionmentioning
confidence: 99%